Causative and their passives in Sanskrit - Lowe, JJ; Molina-Munoz, A; Ruppel, A (CSLI Publications, 2020)
We discuss data on causative constructions and their passives in Sanskrit. Sanskrit is unusual in licensing two different causative constructions for most verbs, together with corresponding passives. We explore the formal analysis of these patterns in argument structure terms, formalized within the argument structure proposals of Kibort (2007) and the approach to causative argument structure proposed by Lowe and Birahimani (2019).